Penyuluhan Perilaku CERDIK dan PATUH sebagai Upaya Penanggulangan Hipertensi pada Lansia di Desa Tonasa, Takalar - Nurmala Sari; Laela Alfionita Dewi; Rafliansyah Rafliansyah; Asifah Baiq Ramadani; Fatimah Azzahrah Zainuddin; Maisya Finistri Marzuki; Dian Fahira Syam; Khairunnisa Assyarifah (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Non-communicable diseases are one of the leading causes of death in the world. Hypertension is one of the trigger factors for the occurrence of several non-communicable diseases that are generally experienced by the elderly. Preventive measures are needed in this case, knowledge also affects this so it is necessary to hold counseling. The purpose of this counseling is to educate the target regarding CERDIK and PATUH behavior as an effort to prevent and control hypertension in the elderly. The service is carried out through several stages, namely the planning stage, the implementation stage and the evaluation stage. The implementation of counseling uses the help of communication media in the form of posters. While the evaluation of the extension was assisted by pre-post test questionnaires which were distributed to respondents. The target in this counseling is the elderly as many as 14 people in Tonasa Village. The value of the results of the pre-post test was then analyzed using the Wilcoxon test. The test results show an increase in the average knowledge of the respondents from 6.9 to 8.9.